2014
DOI: 10.1175/jamc-d-13-0270.1
|View full text |Cite
|
Sign up to set email alerts
|

A Global Land Cover Climatology Using MODIS Data

Abstract: Global land cover data are widely used in weather, climate, and hydrometeorological models. The Collection 5.1 Moderate Resolution Imaging Spectroradiometer (MODIS) Land Cover Type (MCD12Q1) product is found to have a substantial amount of interannual variability, with 40% of land pixels showing land cover change one or more times during 2001–10. This affects the global distribution of vegetation if any one year or many years of data are used, for example, to parameterize land processes in regional and global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
204
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(212 citation statements)
references
References 35 publications
4
204
0
4
Order By: Relevance
“…1) were cumulative starting on the earliest DOY were data were available (DOY 105) for all years (2010)(2011)(2012)(2013)(2014)(2015). This watershed is 32,375 km 2 of which 91% is classified as agricultural use, mostly maize and soy production (Broxton et al 2014). We used the zoo R package to linearly interpolate across missing Q data (Moatar and Meybeck 2005).…”
Section: Data Setsmentioning
confidence: 99%
“…1) were cumulative starting on the earliest DOY were data were available (DOY 105) for all years (2010)(2011)(2012)(2013)(2014)(2015). This watershed is 32,375 km 2 of which 91% is classified as agricultural use, mostly maize and soy production (Broxton et al 2014). We used the zoo R package to linearly interpolate across missing Q data (Moatar and Meybeck 2005).…”
Section: Data Setsmentioning
confidence: 99%
“…Detection of placid open water with SAR data is relatively straight forward because a transmitted radar pulse specularly reflects away from a side-looking SAR antenna giving the water very low values of backscatter [20]. The training site for open water was in the region of very dark radar pixels in the southern part of the lake and classified by the 0.5 km MODIS-based Global Land Cover Climatology [21] as open water. The training site for dry vegetation was in the region outside of the lake boundaries and classified by the 0.5 km MODIS-based Global Land Cover Climatology [21] as grassland.…”
Section: Lake Area Estimation Using Esa Sentinel-1a C-band Radar Datamentioning
confidence: 99%
“…The training site for open water was in the region of very dark radar pixels in the southern part of the lake and classified by the 0.5 km MODIS-based Global Land Cover Climatology [21] as open water. The training site for dry vegetation was in the region outside of the lake boundaries and classified by the 0.5 km MODIS-based Global Land Cover Climatology [21] as grassland. The training site for flooded vegetation was at the discharge of the Komadougou Yobe (also known as the Yobe) River.…”
Section: Lake Area Estimation Using Esa Sentinel-1a C-band Radar Datamentioning
confidence: 99%
“…Given that the surface R n is closely related to the land cover type, MCD12Q1 [37] land cover type data were used in this study, as shown in Figure 2 for reference. Data from all those networks were checked site by site, and some extremely abnormal values were removed.…”
Section: Land Cover Type Datamentioning
confidence: 99%
“…Given that the surface Rn is closely related to the land cover type, MCD12Q1 [37] land cover type data were used in this study, as shown in Figure 2 for reference. …”
Section: Land Cover Type Datamentioning
confidence: 99%